Halogenase-Targeted Genome Mining Leads to the Discovery of (±) Pestalachlorides A1a, A2a, and Their Atropisomers - Mengna Luo; Mengyuan Wang; Shanshan Chang; Ning He; Guangzhi Shan; Yunying Xie (MDPI AG, 2022)
Genome mining has become an important tool for discovering new natural products and identifying the cryptic biosynthesis gene clusters. Here, we utilized the flavin-dependent halogenase GedL as the probe in combination with characteristic halogen isotope patterns to mine new halogenated secondary metabolites from our in-house fungal database. As a result, two pairs of atropisomers, pestalachlorides A1a (1a)/A1b (1b) and A2a (2a)/A2b (2b), along with known compounds pestalachloride A (3) and SB87-H (4), were identified from Pestalotiopsis rhododendri LF-19-12. A plausible biosynthetic assembly line for pestalachlorides involving a putative free-standing phenol flavin-dependent halogenase was proposed based on bioinformatics analysis. Pestalachlorides exhibited antibacterial activity against sensitive and drug-resistant S. aureus and E. faecium with MIC values ranging from 4 μg/mL to 32 μg/mL. This study indicates that halogenase-targeted genome mining is an efficient strategy for discovering halogenated compounds and their corresponding halogenases.